The role of production sharing and trade in the transmission of the great recession - Jacob Wibe (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2012)
The great recession of 2008-2009 resulted in a large fall in trade relative to output. Real trade fell roughly three times more than real GDP in the U.S. and Mexico, and by a factor of five in Canada. The decline in trade and output was particularly large in sectors with high levels of production sharing (goods produced in multiple, sequential stages in more than one country). Motivated by these observations, this paper asks two quantitative questions: 1) What was the role of trade in the transmission of the recession in North America? 2) What was the contribution of production sharing to the large fall in trade? To answer these questions this paper develops a quantitative open economy model of production sharing. The benchmark calibration can account for 72% of the fall in output in Canada, 19% of the fall in output in Mexico, and about two-thirds of the fall in trade for both countries. In the quantitative exercises production sharing can account for 40% of the fall in trade.
Keywords: F4; F1; 330; Konjunktur; Transmissionsmechanismus; Sozialprodukt; Gesamtwirtschaftliche Produktion; Außenwirtschaft; Internationale Arbeitsteilung; Kleines-offenes-Land; Nordamerika; USA; Kanada; Mexiko